2022
DOI: 10.3389/fnins.2022.972918
|View full text |Cite
|
Sign up to set email alerts
|

Decoding competitive endogenous RNA regulatory network in postoperative cognitive dysfunction

Abstract: Postoperative cognitive dysfunction (POCD) is a common postoperative neurological complication in elderly patients. Circular RNAs (circRNAs) are abundant in the mammalian brain and can probably regulate cognitive function. However, the competitive endogenous RNA (ceRNA) regulatory network in POCD remains illiterate. Transcriptomic signatures in the hippocampus of POCD mice derived from the Gene Expression Omnibus (GEO) dataset GSE190880, GSE95070, and GSE115440 were used to identify the circRNA, miRNA, and mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The open field test (OFT) was used to rule out the possibility that laparotomy-primed cognitive impairment arose from variations in spontaneous locomotor activity. 52 On the fourth day after surgery, the animals were placed in an open field apparatus (100 × 100 × 45 cm 3 ). The rats were individually placed in the center of the apparatus and allowed for 5 min free exploration.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The open field test (OFT) was used to rule out the possibility that laparotomy-primed cognitive impairment arose from variations in spontaneous locomotor activity. 52 On the fourth day after surgery, the animals were placed in an open field apparatus (100 × 100 × 45 cm 3 ). The rats were individually placed in the center of the apparatus and allowed for 5 min free exploration.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Spatial learning and memory were assessed using the MWM test 5−10 d post laparotomy. 52 A 6 cm diameter hidden platform in the center of the fourth quadrant was submerged in a circular pool 160 cm in diameter and 50 cm in height. The MWM test comprised two phases: training four times per day for five consecutive days and probe trials without a platform on the sixth day.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that certain circRNAs were found to be aberrantly expressed in hippocampus, playing a role in POCD through ceRNA network ( Wu et al, 2021 ). A series of circRNAs were found to regulate hub genes such as Rbm47, Sostdc1, Egfr, Prkacb, Unc13c, Tbx20 and St8sia2 through ceRNA networks, participating in Wnt, P53 and NF-κB signaling pathways, associating with the development of POCD (At the Hop 50's Rock 'n' Roll, 1996; Cao et al, 2020 ; Wu et al, 2021 ; Wang et al, 2022 ). Although accumulating evidence explained the regulatory function of circRNAs in the brain, their roles in the perioperative context are still unknown area to be explored.…”
Section: Introductionmentioning
confidence: 99%